Nize Isabel de Moraes: memoiris of a historian specializing in Senegambia - Farias, Juliana Barreto; Lopes, Maria Aparecida de Oliveira [UNESP] (Fundacao Getulio Vargas-fgv, 2022)
Between 1960 and 2015, Nize Izabel de Moraes, a historian from Sao Paulo, lived in Dakar (Senegal) and worked as a researcher at the Institut Fondamental d'Afrique Noir (IFAN), at the current Universite Cheikh Anta Diop. Exploring her private archive and other records in Brazil and Senegal, with emphasis on her dia-ries, correspondence and notes on her research and travels between Africa and Europe, the purpose of this article is to analyze her academic trajectory, as well as the impact of her production for the historiography of Senegambia, an area in which she stood out as a pioneering researcher. In this journey, we will point out the silences surrounding her life and work, as well as question her experience as a black intellectual in national and international networks of dialogues, marked by the intercessions of gender, race and nationality.
Keywords: Senegal; Brazil; Trajectory; Black intellectual; Nize Isabel de Morais; Historian